Molecular data show conserved DNA locations distinguishing lung cancer subtypes and regulation of immune genes. (August 2020) - Hurkmans, Daan P.; Tamminga, Menno; van Es, Bram; Peters, Tom; Karman, Wouter; van Wijck, Rogier T.A.; van der Spek, Peter J.; Tauber, Tjebbe; Los, Maureen; van Schetsen, Anouk; Vu, Thu; Hiltermann, T. Jeroen. N.; et al.
Highlights: Lung cancer subtypes are differentiated by conserved methylated loci. Immune modulating genes with ks-score ≥ 70 % are under methylation control. Lung cancer exhibits selective suppression of antigen presentation and processing. Abstract: Introduction: Non-small-cell lung cancer exhibits a range of transcriptional and epigenetic patterns that not only define distinct phenotypes, but may also govern immune related genes, which have a major impact on survival. Methods: We used open-source RNA expression and DNA methylation data of the Cancer Genome Atlas with matched non-cancerous tissue to evaluate whether these pretreatment molecular patterns also influenced genes related to the immune system and overall survival. Results: The distinction between lung adenocarcinoma and squamous cell carcinoma are determined by 1083 conserved methylation loci and RNA expression of 203 genes which differ for >80 % of patients between the two subtypes. Using the RNA expression profiles of 6 genes, more than 95 % of patients could be correctly classified as having either adeno or squamous cell lung cancer. Comparing tumor tissue with matched normal tissue, no differences in RNA expression were found for costimulatory and co-inhibitory genes, nor genes involved in cytokine release. However, genes involved in antigen presentation had a lower expression and a wider distribution in tumor tissue. Discussion: Only a small number of genes, influenced by DNA methylation, determine the lung cancer subtype. The antigen presentation of cancer cells is dysfunctional, while other T cell immune functions appear to remain intact.